Sipe. - Sipe; Sipe; Santapukki, Simo, 1977-; Ahtiainen, Sanna; Eriksson, Anna, 1977-; Kangasjärvi, Mikko, 1972-; Lahti, Pentti, 1945-; Liimatta, Tommi; Marttila, Janne (viulisti); Nyman, Marzi, 1979-; Perelló, Henrik, 1969-; Pohjolainen, Seppo Alvari, 1962-; et al. (Lahti : Levy-yhtiö, 2002)
10 kappaletta.
Laulujen sanat tekstiliitteessä.
Laulujen sanat tekstilipukkeessa.
Sanat tekstiliitteessä.
Sipe (dr, b, g, perc, p, synt, melodika, kazoo, voc), Tommi Liimatta (voc, dobro), Gösta Sundqvist,Hannu Sallinen, Timo Rautiainen, Sami Yli-Pihlaja, Toni Wirtanen, Anna Eriksson (voc), Haije Sundqvist, Tanjalotta Räikkä, Seppo Pohjolainen (taustalaulu), Marzi Nyman (g), Mikko Kangasjärvi (keyb), Pentti Lahti (as, ts, bs, cl, fl, picc), Markku Renko (tp, fl-h), Henrik Perello, Miia Tepponen, Sanna Ahtiainen, Janne Marttila (v), Cleaning Women (pyykinkuivaustelineet).
Sipe (voc, säv., san., sov...) sekä Tommi Liimatta (voc, dobro), Gösta Sundqvist (voc), Hannu Sallinen (voc), Timo Rautiainen (voc), Toni Wirtanen (voc), Anna Eriksson (voc), Marzi Nyman (g), Mikko Kangasjärvi (keyb)...
Sipe (rummut, bassokitara, kitara, lyömäsoittimet, syntetisaattori, sähköpiano, omnichord, melodica, kazoo, lauluääni). Liimatta, Tommi (lauluääni, dobro /01). Sundqvist, Gösta (lauluääni /02). Sallinen, Hannu (lauluääni /03,05,09). Rautiainen, Timo (lauluääni /04). Pohjolainen, Seppo (taustalaulu /04). Yli-Pihlaja, Sami (lauluääni /06). Wirtanen, Toni (lauluääni /07). Eriksson, Anna (lauluääni /10). Nyman, Markus 'Marzi' (kitara). Cleaning Women (yhtye). Kangasjärvi, Mikko (kosketinsoittimet). Lahti, Pentti (alttosaksofoni, tenorisaksofoni, baritonisaksofoni, bassoklarinetti, huilu, pikkolohuilu, bassohuilu). Renko, Markku (trumpetti, piccolotrumpetti, flyygelitorvi). Perello, Henrik (viulu). Tepponen, Miia (viulu). Ahtiainen, Sanna (viulu). Janne Marttila (viulu). Sundqvist, Haije (taustalaulu /02). Räikkä, Tanjalotta (taustalaulu /02).
Keywords: rock